English Teacher Perception of Implementation Kurikulum Merdeka in English Teaching Learning Process - Lestari, Dian Puji; Lestari, Siti; Nularsih, Nularsih (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research was aimed to determine English teachers’ perception of implementation Kurikulum Merdeka in English teaching learning process at SMP N 6 Semarang. This study was conducted by descriptive qualitative method. The data were collected by interview 3 English teachers at SMP N 6 Semarang who implementing Kurikulum Merdeka. The results showed that Kurikulum Merdeka has impact in English teaching learning process. The entire English teachers make Tujuan Pembelajaran based on Capaian Pembelajaran in Kurikulum Merdeka. The teachers have also implemented a learning cycle, differentiated learning, and conducted assessment based on Kurikulum Merdeka. Although all English teachers have different perception on some categories, but they said that Kurikulum Merdeka has impact in English teaching learning process especially in students learning outcomes